Early outcomes of moderate-to-high-risk pediatric congenital cardiac surgery and predictors of extracorporeal circulatory life support requirement - Deng, Mimi Xiaoming; Haller, Christoph; Moss, Kasey; Saha, Sudipta; Runeckles, Kyle; Fan, Chun-Po Steve; Langanecha, Bhavikkumar; Floh, Alejandro; Guerguerian, Anne-Marie; Honjo, Osami (Frontiers in Pediatrics, 2024)
Background: Cardiopulmonary failure refractory to medical management after moderate-high risk congenital cardiac surgery may necessitate mechanical support with veno-arterial extracorporeal membrane oxygenation (ECMO). On the extreme, ECMO can also be initiated in the setting of cardiac arrest (ECPR) unresponsive to conventional resuscitative measures. Methods: This was a single-center retrospective cohort study of patients (n = 510) aged < 3 years old who underwent cardiac surgery with cardiopulmonary bypass (CPB) with a RACHS-1 score ≥ 3 between 2011-2014. Perioperative factors were reviewed to identify predictors of ECMO initiation and mortality in the operating room (OR) and in the intensive care unit (ICU). Results: 510 patients with mean surgical age of 10.0 ± 13.4 months were included. 21 (4%) patients received postoperative ECMO - 12 were initiated in the OR and 9 in the ICU. ECMO cannulation was associated with cardiopulmonary bypass duration, aortopulmonary shunt, residual severe mitral regurgitation, vaso-inotropic score and post-procedural lactate (p < 0.001). Of the 32 (6%) total deaths, 7 (22%) were ECMO patients – 4 were elective OR cannulations and 3 were ICU ECPR. Prematurity (hazard ratio [HR]: 2.61, p < 0.01), Norwood or Damus-Kaye-Stansel procedure (HR 4.29, p < 0.001), postoperative left ventricular dysfunction (HR 5.10, p = 0.01), residual severe tricuspid regurgitation (HR 6.06, p < 0.001), and postoperative ECMO (ECPR: HR 15.42, p < 0.001 vs. elective: HR 5.26, p = 0.01) were associated with mortality. The two patients who were electively cannulated in ICU survived. Conclusion: Although uncommon, postoperative ECMO in children after congenital cardiac surgery is associated with high mortality, especially in cases of ECPR. Patients with long cardiopulmonary bypass time, residual cardiac lesions, or increased vaso-inotropic requirement are at higher risk of receiving ECMO. Pre-emptive or early ECMO initiation before deterioration into cardiac arrest may improve survival.